Pre Vertical Jump Performance to Regulate the Training Volume - Claudino, J. G.; Mezêncio, B.; Soncin, R.; Ferreira, J. C.; Couto, B. P.; Szmuchrowski, L. A. (International Journal of Sports Medicine, 2012)
The purpose of this study was to assess the effect of training load regulation, using the CMJ at the beginning of the session, on the total plyometric training load and the vertical jump performance. 44 males were divided into 4 groups: No Regulation Group (nRG), Regulation Group (RG), Yoked Group (YG) and Control Group (CG). The nRG received 6 weeks of plyometric training, with no adjustment in training load. The RG underwent the same training; however, the training load was adjusted according to the CMJ performance at the beginning of each session. The adjustment made in RG was replicated for the volunteers from the corresponding quartile in the YG, with no consideration given to the YG participant’s condition at the beginning of its session. At the end of the training, the CMJ and SJ performance of all of the participants was reassessed. The total training load was significantly lower (p=0.036; ES=0.82) in the RG and the YG (1905±37 jumps) compared to the nRG (1926±0 jumps). The enhancement in vertical jump performance was significant for the groups that underwent the training (p<0.001). Vertical jump performance, performed at the beginning of the session, as a tool to regulate the training load resulted in a decrease of the total training load, without decreasing the long-term effects on vertical jump performance.
Keywords: countermovement jump; adjustment; monitoring; load regulation; plyometric training